INDUSTRIAL RELATIONS STRATEGIES IN PREVENTING VIOLATION OF JOINT WORK AGREEMENT (PKB) (CASE STUDY ON BANK ‘X’ IN BANDUNG) - Deni Suherman (LPPM POLITEKNIK LP3I BANDUNG, 2018)
Joint Working Agreement (PKB), which is a commitment of engagement between workers represented by the Workers 'Association and employers represented by employers' associations in order to respect, regulate the harmonization of the rights and obligations of both parties within the framework of industrial relations can not guarantee the absence of violations. The violation of the Joint Working Agreement (PKB) raises the idea of the need for an appropriate Industrial Relations strategy from both parties involved, knowing how much the relationship between the industrial relations strategy and the prevention of collective labor agreements (PKB) requires research. The result of the research concludes that there is a strong correlation between industrial relations strategy with prevention of collision of collective work agreement (PKB) with value r = 0,679 and result of hypothesis test concluding rejection of Ho and acceptance of Ha